Paleoglacial footprint and fluvial terraces of the Shaluli Shan, SE Tibetan Plateau. Issue 2 (1st December 2021) - Schneider, R. A. A.; Blomdin, R.; Fu, P.; Xu, X.K.; Stroeven, A. P.
ABSTRACT: This study provides mapping of glacial and fluvial geomorphology in the Shaluli Shan region on the eastern margin of the south-eastern Tibetan Plateau. Based on TanDEM-X 12 m elevation data and GoogleEarth imagery, glacial valleys, ice-marginal moraines, glacial lineations, scoured terrain and fluvial terraces were mapped. Covering around 11, 000 km 2, this map is the first for this region to display geomorphology at a spatial resolution of 0.4 arcsec (= c. 11 m) and to include fluvial terraces. Its glacial landform distribution is largely consistent with previous mapping. The substantially higher level of detail in this study is reflected in an approximately tenfold number and smaller median sizes of individual landforms such as moraines and glacial lineations. These results underscore the importance of high-resolution DEM data such as TanDEM-X for the identification of glacial and fluvial geomorphology. The map presented here will be used for detailed paleoglacial reconstructions and landscape evolution studies combining both glacial and fluvial landforms.